1949
DOI: 10.1021/ed026p307
|View full text |Cite
|
Sign up to set email alerts
|

The training of a chemist (inorganic).

Abstract: Early in 1948 the authors began a study of the content of the usual course in freshman chemistry in the United States. We hoped at the same time to gather a good deal of information about the status of inorganic chemistry in relation to chemistry as a whole. Accordingly, a survey questionnaire was sent to 60 departments of chemistry accredited by the A. C. S., selected from the list published in Chem. Eng. News, 25, 3888 (1947).Fifty replies were received, although some were not complete. All figures are for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1950
1950
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…It was assumed that general chemistry would provide instruction in basic inorganic chemistry, which at the time consisted of descriptive chemistry and qualitative analysis . Recognizing that the general course had evolved and inorganic chemistry had advanced as a field, the inorganic chemistry community began a concerted effort to advocate for a separate and additional course in inorganic chemistry. , A symposium titled “The Place of Inorganic Chemistry in the Undergraduate Curriculum” was held at the 116th meeting of the ACS in 1949, and reflections on the nature of these proposed courses and current practices at individual institutions were published in JCE . , Even at this point, it is clear that there was little standardization in the curriculum; institutions developed curricula that met their local needs.…”
Section: A Brief History Of Time: the Changing Inorganic Curriculummentioning
confidence: 99%
“…It was assumed that general chemistry would provide instruction in basic inorganic chemistry, which at the time consisted of descriptive chemistry and qualitative analysis . Recognizing that the general course had evolved and inorganic chemistry had advanced as a field, the inorganic chemistry community began a concerted effort to advocate for a separate and additional course in inorganic chemistry. , A symposium titled “The Place of Inorganic Chemistry in the Undergraduate Curriculum” was held at the 116th meeting of the ACS in 1949, and reflections on the nature of these proposed courses and current practices at individual institutions were published in JCE . , Even at this point, it is clear that there was little standardization in the curriculum; institutions developed curricula that met their local needs.…”
Section: A Brief History Of Time: the Changing Inorganic Curriculummentioning
confidence: 99%
“…Selwood in 1939 (19) and Sisler in 1948 (20) were still pleading for teachers to use modern theoretical principles as the organizing basis of the course because descriptive chemistry was "dull". A study published in 1949 (16) reporting on general chemistry courses in 60 departments having programs approved by the American Chemical Society described the majority of the courses as "tending towards a very elementary study of physical-chemical principles with such descriptive material as is necessary to understand the principles". Another survey of 65 institutions in 1954 (21) found that only 15% of class time was spent on metals, nonmetals, and their compounds.…”
Section: Courses Of the New Curriculummentioning
confidence: 99%
“…The changing nature of chemistry as a science precipitated the first change, which began after the First World War and continued into the 1950's (16). The description of the nuclear atom by Rutherford, the discovery of the neutron, the Debye-Huckel principle of strong electrolytes, and the Bronsted-Lowry acid-base principle gave new meaning to the properties of atoms and isotopes, the concepts of salts and hydrolysis, and the significance of the periodic table.…”
mentioning
confidence: 99%
“…In connection with the informative series of articles and symposia which have appeared during the last few years in This Journal (See, e. g., 1~4, 7,[10][11][12] dealing with methods of instruction and research activities in the different fields of chemistry at various institutions, the following account of the program of graduate study and research in inorganic chemistry at the Massachusetts Institute of Technology may be of interest.…”
mentioning
confidence: 99%